Length-dependent pleural inflammation and parietal pleural responses after deposition of carbon nanotubes in the pulmonary airspaces of mice. Issue 6 (September 2012) - Murphy, Fiona A.; Poland, Craig A.; Duffin, Rodger; Donaldson, Ken
Abstract Background: Carbon nanotubes (CNT) are fibre-like nanomaterials whose structural similarity to asbestos has raised concerns that they may also pose a mesothelioma hazard. The objective of this study was to examine the inflammatory potential of three CNT samples of differing length on the lungs and pleural cavity following introduction into the airspaces of mice. ResultsAspiration of the two short/tangled and one long CNT sample into the lungs of mice resulted in a length-dependent inflammatory response at 1 week, i.e., only the long CNT sample caused acute neutrophilic inflammation in bronchoalveolar lavage at 1 week and progressive thickening of the alveolar septa. The authors also report length-dependent inflammatory responses in the pleural lavage after exposure only to the long CNT. The inflammatory response in the pleural cavity to long fibres and the appearance of lesions along the chest wall and diaphragm was not present at 1 week and only evident by 6 weeks post-exposure. Conclusion: Length-dependent pathogenicity is a feature of asbestos and the results presented in this study demonstrate similar length-dependent pathogenicity of CNT in the lungs and pleural space following airspace deposition. The data support the contention that long CNT reach the pleura from the airspaces, and that they are retained at the parietal pleura and cause inflammation and lesion development. The parietal pleura is the site of origin of mesothelioma and inflammation is considered to be a process involved in asbestos carcinogenesis and so the data support the contention that CNT may pose an asbestos-like mesothelioma hazard.